Identification of mRNA Prognostic Markers for TGCT by Integration of Co-Expression and CeRNA Network - Zhu, Fang; Liu, Zhizhong; Zhou, Qianyin; Fan, Jingyu; Zhou, Dai; Xing, Liu; Bo, Hao; Tang, Le; Fan, Liqing (Frontiers in Endocrinology, 2021)
Testicular germ cell tumor (TGCT) is the most common malignant tumor in young men and is associated with poor prognosis. We assessed the RNA expression profiles of 13 TGCT tissues and 4 adjacent normal tissues by transcriptome sequencing to identify novel prognostic biomarkers. We detected several differentially expressed mRNAs in TGCT that were functionally annotated by GO and KEGG enrichment analyses to tumorigenesis-related processes such as immunity and chemotherapeutic resistance. An mRNA-lncRNA-miRNA regulatory network was constructed using RNA-Seq data and public databases, and integrated with TCGA database to develop a prediction model for metastasis and recurrence. Finally, GRK4, PCYT2 and RGSL1 were identified as predictive markers of survival and therapeutic response. In conclusion, we found several potential predictors for TGCT prognosis and immunotherapeutic response by ceRNA network analysis.